The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1155/2017/6825250
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Pitting Corrosion Resistance of AISI 316LVM Steel with Ta-Hf-C/Au Bilayers for Biomedical Applications

Abstract: Tantalum carbide (TaC), hafnium carbide (HfC), and Ta-Hf-C mixed coatings with and without a gold (Au) interlayer were deposited on 316LVM steel substrates by the magnetron cosputtering technique in order to improve the corrosion resistance of steel substrates in a simulated biological fluid. To study the effect of the gold interlayer on pitting corrosion, the different systems were placed in contact with Ringer’s solution at pH 7.4 and a temperature of 37°C. The electrochemical properties of the coatings were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…The authors [43,[53][54][55][56] consider that nanocomposite coatings have undeniable advantages due to the nanostructuring of the applied coatings. Multi-layer coatings [58] create an additional barrier. This is explained by the fact that, due to the All these factors testify to increased corrosion resistance of stainless-steel specimens with Al-Si-N and Al-Si-N-O/Al-Si-O coatings, which ultimately increases for the multilayer coating, as compared to uncoated specimens.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors [43,[53][54][55][56] consider that nanocomposite coatings have undeniable advantages due to the nanostructuring of the applied coatings. Multi-layer coatings [58] create an additional barrier. This is explained by the fact that, due to the All these factors testify to increased corrosion resistance of stainless-steel specimens with Al-Si-N and Al-Si-N-O/Al-Si-O coatings, which ultimately increases for the multilayer coating, as compared to uncoated specimens.…”
Section: Resultsmentioning
confidence: 99%
“…The authors [43,[53][54][55][56] consider that nanocomposite coatings have undeniable advantages due to the nanostructuring of the applied coatings. Multi-layer coatings [58] create an additional barrier. This is explained by the fact that, due to the different chemical composition of each of the layers, barriers arise that prevent the development of a leading channel for the corrosive environment penetration (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…ASTM F138 and ASTM F139 are the designations of implant-quality stainless steels for orthopedic applications [6]. However, despite the attractiveness of stainless steel devices, it is well-known that they are prone to localized corrosion in the human body due to chloride-induced pitting attack [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the requirement for improving the wear resistance, the PVD technique has allowed the deposition of thin films that modify the physical and chemical properties of the surface without modifying the mechanical properties of the substrate [ 10 , 11 , 12 ]. The use of tantalum as a biomaterial has good acceptance due to improvement in the corrosion resistance and wear resistance, and it also has good biocompatibility inside the human body [ 13 , 14 ]. Likewise, different studies have shown the significant applicability of tantalum as a coating because it exhibits similar mechanical properties as bone, such as high hardness and flexibility.…”
Section: Introductionmentioning
confidence: 99%